Rancang Bangun Komponen Sandbox pada Game Unity dengan Menerapkan Design Patterns dan Arsitektur Microservices - Andhik Ampuh Yunanto; Fadilah Fahrul Hardiansyah; Adhiemas Andira Anantha Putra; Maulidan Bagus Afridian Rasyid; Ramadhany Candra Arif Putra (Teknik Informatika Universitas Pamulang, 2021)
Currently the game has covered a very broad market needs where games offer video content, products, Virtual Reality, and special events and game competitions. This offer is what triggers an increase in sales and an increase in revenue in the gaming industry. Due to increasingly fierce competition, game development companies must develop their products quickly and precisely in order to compete in today's game industry. However, rapid product development and the application of proper architecture are also problems, especially the products being developed are games with simulation or sandbox themes that have a high level of complexity. So we need an application that helps game development, especially the development of the sandbox component. The purpose of this study is to provide a library that helps the development of the sandbox component, where this library will apply the Design Patterns and Microservices Architecture to simplify the maintenance and development period of the game after release. This research is also working with the company for the development and validation. This research will develop several sandbox components and will apply a Design Pattern to each component. This proposed method has been tested by users who are experts in developing games. The results show that the application of the proposed method can be implemented and can run well. And the system built also gets a score with an average above 80% and good feedback from expert users. So that this research is expected to become an application that can help programmers later in developing a game application that is good and appropriate. As well as the applications built in this study can also provide recommendations in terms of development methods.